The best of titles: A revolution in the vision of the history of water in Mexico - García Acosta, María (2006)
The historiography of water in Mexico begins with the 20th century, is linked to government plans and projects, and is elaborated by builders and chroniclers. These works transcended the Porfiriato and the Revolution, and saw the use of water for irrigation as one of the pillars for national economic development (Herrera y Lasso, Palacios, Gazol, Orive Alba and López Zamora).